Mentoring the Next Generation of Health Professionals: A Mentor-the-Mentor Approach - Andrea L. DeMaria; Stephanie Meier; Jaziel L. Ramos-Ortiz (New Prairie Press, 2019)
The purpose of this commentary is to share team-based mentoring strategies used for successful interdisciplinary research team productivity and sustainability. This commentary lists and describes the top ten considerations for building a productive mentor-the-mentor approach, inspired by the train-the-trainer method. The approach promotes reciprocal training and individualized experiences, while producing positive professional and personal outcomes. We pinpoint how relationship-building rooted in passion and clear communication, explicit expectations and regular celebrations, and routine paired with a bit of play enhances productivity and encourages future health professionals to emerge as leaders in the field.